The Medieval World - Linehan, Peter, editor.
1 online resource
Keywords: "Ranging from Connacht to Constantinople and from Tynemouth to Timbuktu, the forty-four contributors to The Medieval World seek to bring the Middle Ages to life, offering definitive appraisals of the distinctive features of the period. This second edition includes six additional chapters, covering the Byzantine empire, illuminated manuscripts, the 'ésprit laïque' of the late middle ages, saints and martyrs, the papal chancery, and scholastic thought.? Chapters are arranged thematically within four parts:1. Identities, Selves and Others 2. Beliefs, Social Values and Symbolic Order 3. Power and Power-Structures 4. Elites, Organisations and GroupsThe Medieval World presents the reader with an authoritative account of original scholarship across the medieval millennium and provides essential reading for all students of the subject."--Provided by publisher.